2019
DOI: 10.3390/pharmaceutics11050219
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Efficiency of Antitumor Agents in Ovarian Cancer Spheroids: The Case of Recombinant Targeted Toxin DARPin-LoPE and the Chemotherapy Drug, Doxorubicin

Abstract: The efficiency of delivering a therapeutic agent into a tumor is among the crucial factors determining the prospects for its clinical use. This problem is particularly acute in the case of targeted antitumor agents since many of them are high-molecular-weight compounds. In this work, the penetration of therapeutic agents of two distinct molecular weights into the spheroids of ovarian adenocarcinoma overexpressing human epidermal growth factor receptor 2 (HER2) was studied. It was shown that the low-molecular-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…When selecting the drugs, we also considered their molecular size. Previous studies have shown that using two anticancer compounds with different molecular weights reduces the penetration efficiency of the high molecular weight agents [56]. In our case, by using the two compounds, both with low molecular weights, we showed that either separate or combination treatments are efficient against the spheroids.…”
Section: Discussionsupporting
confidence: 58%
“…When selecting the drugs, we also considered their molecular size. Previous studies have shown that using two anticancer compounds with different molecular weights reduces the penetration efficiency of the high molecular weight agents [56]. In our case, by using the two compounds, both with low molecular weights, we showed that either separate or combination treatments are efficient against the spheroids.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, we obtained a new type of theranostic nanocomplexes based on UCNP coated with PEG and functionalized with the recombinant targeted toxin DARPin-LoPE [ 40 , 42 ]. Selective binding of UCNP-DARPin-LoPE nanocomplexes to HER2-overexpressing human breast adenocarcinoma cells was shown.…”
Section: Discussionmentioning
confidence: 99%
“…Selective binding of UCNP-DARPin-LoPE nanocomplexes to HER2-overexpressing human breast adenocarcinoma cells was shown. Besides, a significant decrease in cancer cell viability was revealed due to the selective action of the targeted toxin DARPin-LoPE by blocking protein biosynthesis [ 42 ] (see also Figure S3 ). The demonstrated ability of the obtained nanocomplexes to visualize tumors indicates their potential as agents for bioimaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations